Key infection stages defending heat stress in high-temperature-resistant Blumeria graminis f. sp. tritici isolates - Zhang, Meihui; Wang, Aolin; Zhang, Cheng; Xu, Fei; Liu, Wei; Fan, Jieru; Ma, Zhanhong; Zhou, Yilin (Frontiers in Microbiology, 2022)
With the increase of temperature in the winter wheat-growing regions in China, the high-temperature-resistant Blumeria graminis f. sp. tritici (Bgt) isolates developed in the fields. To clarify the key infection stages and the roles of heat shock protein (HSP) genes of high-temperature-resistant Bgt isolates defending high temperature, 3 high-temperature-resistant and 3 sensitive Bgt isolates were selected from 55 isolates after determination of temperature sensitivity. And then they were used to investigate the infection stages and the expression levels of HSP genes, including Bgthsp60, Bgthsp70, Bgthsp90, and Bgthsp104, at 18°C and 25°C. The formation frequency of abnormal appressoria and inhibition rate of haustoria formation of high-temperature-resistant isolates at 25°C were lower than those of high-temperature-sensitive isolates, while major axis of microcolonies of high-temperature-resistant isolates was higher than those of high-temperature-sensitive isolates at 25°C. The results indicated that haustoria formation and hyphal expansion were the key infection stages of defense against heat stress in high-temperature-resistant isolates. Further analyses of HSP genes found the expression levels of Bgthsp60 and Bgthsp70c were upregulated at 24 and 72 h post-inoculation in high-temperature-resistant isolates, while no significant difference was observed for Bgthsp90 and Bgthsp104 genes. Taken together, the basis of high-temperature-resistant Bgt isolates is associated with induced expression of Bgthsp60 and Bgthsp70c response to heat stress in haustoria formation and hyphal expansion stages.